2013
DOI: 10.3389/fnhum.2013.00694
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Promotes Global Spatial Processing in Habitual and Non-Habitual Caffeine Consumers

Abstract: Information processing is generally biased toward global cues, often at the expense of local information. Equivocal extant data suggests that arousal states may accentuate either a local or global processing bias, at least partially dependent on the nature of the manipulation, task, and stimuli. To further differentiate the conditions responsible for such equivocal results we varied caffeine doses to alter physiological arousal states and measured their effect on tasks requiring the retrieval of local versus g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 106 publications
1
5
0
1
Order By: Relevance
“…The combination of caffeine and theanine did not differ from placebo, suggesting that the 2 compounds negated each other's effects. The results are consistent with recent research suggesting that caffeine accentuates global processing biases in visual perception including the same hierarchical shape task employed in the present experiment (Mahoney et al 2011), language-based tasks (Brunyé et al 2012), and spatial memory tasks (Giles et al 2013). Additionally, emotional arousal, regardless of positive or negative valence, has been shown to augment global spatial processing (Brunyé et al 2009), suggesting that increasing arousal via either caffeine intake or emotion induction magnifies the global processing bias, whereas reducing arousal via theanine intake results in enhanced attention to details.…”
Section: Global Versus Local Processingsupporting
confidence: 82%
See 2 more Smart Citations
“…The combination of caffeine and theanine did not differ from placebo, suggesting that the 2 compounds negated each other's effects. The results are consistent with recent research suggesting that caffeine accentuates global processing biases in visual perception including the same hierarchical shape task employed in the present experiment (Mahoney et al 2011), language-based tasks (Brunyé et al 2012), and spatial memory tasks (Giles et al 2013). Additionally, emotional arousal, regardless of positive or negative valence, has been shown to augment global spatial processing (Brunyé et al 2009), suggesting that increasing arousal via either caffeine intake or emotion induction magnifies the global processing bias, whereas reducing arousal via theanine intake results in enhanced attention to details.…”
Section: Global Versus Local Processingsupporting
confidence: 82%
“…Our results add to a growing body of evidence showing that caffeine can have beneficial effects on executive control of visual attention (Brunyé et al 2010a(Brunyé et al , 2010bGiles et al 2013;Mahoney et al 2011), as well as add to a relatively new area suggesting that theanine may have calming properties following arousing conditions (Kimura et al 2007;Steptoe et al 2007). The present study is the first, to our knowledge, to show that when exposed to heighted emotional stimuli, theanine and caffeine alone exert differential effects on physiological response and attentional processes, but when consumed together, they counteract the effects of each other.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This strong sense of community that is part of the Rwandan urban lifestyle may also provide another reason why living in Kigali does not increase perceptual bias to the same extent as living in Western cities of comparable size, if stress and the felt 'pace of life' can impact bias. The stress and pace of life of many urban environments may augment arousal (Lederbogen et al, 2011;Linnell, Davidoff, & Caparos, 2014) which, in turn, may increase global bias (Giles, Mahoney, Brunyé, Taylor, & Kanarek, 2013;Mahoney et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The author suggests that right lateralized brain mechanisms responsible for emotion perception may explain why some artists may choose to depict the right cheek of male figures, but the left cheek of female figures, perhaps promoting perceptions of dominance in male figures. The final contribution related to identifying and characterizing lateralized processes was provided by Giles and colleagues in their article Caffeine Promotes Global Spatial Processing in Habitual and Non-habitual Caffeine Consumers (Giles et al, 2013). The authors found that increasing doses of caffeine promoted memory for distal but not proximal landmark relationships during a spatial memory test.…”
Section: Frontiers In Human Neurosciencementioning
confidence: 99%